Developing business strategy at pt proflexy in the global competition - Bayu Irawan, Yuslan; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract -  PT PROFLEXY is a leading manufacturer of flexible packaging as one of the most important global player in the flexible packaging industry. Since periode year of 2010 to 2014 the company faced situation that the gross profit stagnant although the sales revenue is increased. The most of  PT PROFLEXY profit is generated by sales revenue. Base on to the financial report that company have the sales revenue of 60% to the local demand and 40% to the export demand. This target applied by the company remaining that the local demand most generated the profit than the export.But since 2010 the local marketdemand isin saturation market which caused by the global condition in currency depretiation. Regarding to this situation then PT PROFLEXY expand their sales by penetrating potential new markets in Asia, America, Europe, Australia and America. But the strategy is not succesed yet to increase the profit as expected because in point of view the writer that the company has not properly in selecting, targeting and positioning to get the economics operation in competitive global market. In this research the writer propose and recomend the company that tobe a winner in global competition have to do the 3 (three) steps. The first step is company should have and analyse their strength.The second step isthatcompany should have selected the economicsmarket destination by considering in several factors such as GDP, WGI dan LPI, Tax and Duty. These factors are represent of the power of global  buyer, situation & conditions and transportation facilities in each countries destination without ignoring the bilateral and multirateral organization such as WTO, AFTA, etc.The third step is when the destinations are determined then the company should compete in 4 arena of hypercompetition. Base on to this reasearch, finally the writer propose to reprioritize and focused in selected country refer to the company strength to get the profit increasing. Keywords: Sales revenue, Profit, company capabilities, world indicators, hypercompetition